Diagnostic Utility of Non-invasive Tests for Inflammatory Bowel Disease: An Umbrella Review - Shi, Jin-Tong; Zhang, Yuexin; She, Yuehan; Goyal, Hemant; Wu, Zhi-Qi; Xu, Hua-Guo (Frontiers in Medicine, 2022)
Background: To consolidate evidence from published systematic review and meta-analyses evaluating the diagnostic performances of noninvasive tests for inflammatory bowel disease (IBD) in various clinical conditions and age groups. Method: Two independent reviewers systematically indentified and appraised systematic reviews and meta-analyses assessing diagnostic utility of noninvaisve tests for IBD. Each association was categorized as adults, children, and mixed population, based on the age ranges of patients included in the primary studies. We classified clinical scenarios into diagnosis, activity assessment, and predicting recurrence. Results: 106 assessments from 43 reviews were included, with 17 noninvasive tests. Fecal calprotectin(FC) and fecal lactoferrin(FL) were the most sensitive for distinguishing IBD from non-IBD. However, anti-neutrophil cytoplasmic antibodies (ANCA) and FL was the most specific for it. FC and FL were the most sensitive and specific tests respectively to distinguish IBD from irritable bowel syndrome(IBS). Anti-Saccharomyces cerevisiae antibodies (ASCA) IgA was the best test to distiguish Crohn’s disease (CD) to ulcerative colitis (UC). Interferon-γ release assaywas the best test to distinguish CD from intestinal tuberculosis (ITB). Ultrasound (US) and magnetic resonance enterography (MRE) were both sensitive and specific for disease activity, along with high sensitivity of FC. Small intestine contrast ultrasonography (SICUS) had the highest sensitivity, and FC had the highest specificity for operative CD recurrence. Conclusions: In this umbrella review, we summarized the diagnostic performance of noninvasive tests for IBD in various clinical conditions and age groups. Clinicians can use the suggested non-invasive test depending on the appropriate clinical situation in IBD patients.